Large oncosomes overexpressing integrin alpha-V promote prostate cancer adhesion and invasion via AKT activation - Chiara Ciardiello; Alessandra Leone; Paola Lanuti; Maria S. Roca; Tania Moccia; Valentina R. Minciacchi; Michele Minopoli; Vincenzo Gigantino; Rossella De Cecio; Massimo Rippa; Lucia Petti; Francesca Capone; et al. (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Molecular markers for prostate cancer (PCa) are required to improve the early definition of patient outcomes. Atypically large extracellular vesicles (EVs), referred as “Large Oncosomes” (LO), have been identified in highly migratory and invasive PCa cells. We recently developed and characterized the DU145R80 subline, selected from parental DU145 cells as resistant to inhibitors of mevalonate pathway. DU145R80 showed different proteomic profile compared to parental DU145 cells, along with altered cytoskeleton dynamics and a more aggressive phenotype. Methods Immunofluorescence staining and western blotting were used to identify blebbing and EVs protein cargo. EVs, purified by gradient ultra-centrifugations, were analyzed by tunable resistive pulse sensing and multi-parametric flow cytometry approach coupled with high-resolution imaging technologies. LO functional effects were tested in vitro by adhesion and invasion assays and in vivo xenograft model in nude mice. Xenograft and patient tumor tissues were analyzed by immunohistochemistry. Results We found spontaneous blebbing and increased shedding of LO from DU145R80 compared to DU145 cells. LO from DU145R80, compared to those from DU145, carried increased amounts of key-molecules involved in PCa progression including integrin alpha V (αV-integrin). By incubating DU145 cells with DU145R80-derived LO we demonstrated that αV-integrin on LO surface was functionally involved in the increased adhesion and invasion of recipient cells, via AKT. Indeed either the pre-incubation of LO with an αV-integrin blocking antibody, or a specific AKT inhibition in recipient cells are able to revert the LO-induced functional effects. Moreover, DU145R80-derived LO also increased DU145 tumor engraftment in a mice model. Finally, we identified αV-integrin positive LO-like structures in tumor xenografts as well as in PCa patient tissues. Increased αV-integrin tumor expression correlated with high Gleason score and lymph node status. Conclusions Overall, this study is the first to demonstrate the critical role of αV-integrin positive LO in PCa aggressive features, adding new insights in biological function of these large EVs and suggesting their potential use as PCa prognostic markers.